Pengembangan Sistem Cara Produksi Makanan Enteral yang Baik (CPMEB) dan Aplikasinya di Rumah Sakit - Amiroh Amiroh; Winiati Pudji Rahayu; Ratih Dewanti Hariyadi (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2016)
Hospital formula enteral food is a special food targeted specifically for a group of people with health risk. Therefore its safety needs to be controlled more stringently for example through the application Good Manufacturing Practices (GMP). Presently, the guidelines for good processing practices for enteral food is not available yet. This research aims to develop a Good Enteral Food Manufacturing Practices (GEFM) consisting of a guideline as well as a sysstematic audit system that can be applied easily in the hospital. The system was developed based on the Ministry of Health of Republic of Indonesia Regulation Number:1096/MenKes/PER/VI/2011 on hygiene and sanitation for food service industries and other relevant references. Based on the literature review and trials, thirteen aspects were defined for the require- ments; including four main aspects pertaining production room, production equipment, process control and workers' hygiene. Other aspects include building and its facilities, sanitation facility, raw materials storage, monitoring, pest control, distribution, training, patient feeding, and documentation. An audit trial at a hospital Y suggested that its enteral food production unit was categorized as good; but needed improve- ment in several aspects such as: production equipment storage, hygiene and sanitation maintenance, food distribution and food handle training.